Temporal Lobe Spikes Affect Distant Intrinsic Connectivity Networks - Mirandola, Laura; Ballotta, Daniela; Talami, Francesca; Giovannini, Giada; Pavesi, Giacomo; Vaudano, Anna Elisabetta; Meletti, Stefano (Frontiers in Neurology, 2021)
Objective: To evaluate local and distant BOLD signal changes related to interictal epileptiform discharges (IED) in drug-resistant temporal lobe epilepsy (TLE). Methods: Thirty-three TLE patients undergoing EEG-fMRI as part of the presurgical work-up were consecutively enrolled. First, a single-subject spike-related analysis was performed: (a) to verify the BOLD concordance with the presumed Epileptogenic Zone (EZ); and (b) to investigate the Intrinsic Connectivity Networks (ICN) involvement. Then, a group analysis was performed to search for common BOLD changes in TLE. Results: IED were recorded in 25 patients and in 19 (58%) a BOLD response was obtained at single-subject level. In 42% of the cases, BOLD changes were observed in the temporal lobe, although only one patient had a pure concordant finding, with a single fMRI cluster overlapping (and limited to) the EZ identified by anatomo-electro-clinical correlations. In the remaining 58% of the cases BOLD responses were localized outside the temporal lobe and the presumed EZ. In every patient with a spike-related fMRI map at least one ICN appeared involved. Four main ICNs were preferentially involved: motor, visual, auditory/motor speech and the default mode network. At single-subject level, EEG-fMRI proved to have high specificity (above 65%) in detecting engagement of an ICN and the corresponding ictal/post ictal symptom, and high positive predictive value (above 67%) in all networks except the visual one. Finally, the group analysis of IED-related BOLD changes revealed common activations at the right precentral gyrus, supplementary motor area and middle cingulate gyrus. Significance: Interictal temporal spikes affect several distant extra-temporal areas, and specifically the motor/premotor cortex. EEG-fMRI in patients with TLE eligible for surgery is recommended not for strictly localizing purposes rather it might be useful to investigate ICNs alterations at single-subject level.